2017
DOI: 10.1097/gox.0000000000001407
|View full text |Cite
|
Sign up to set email alerts
|

Animation Deformity in Postmastectomy Implant-Based Reconstruction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 19 publications
0
68
0
1
Order By: Relevance
“…Although initially described in patients undergoing breast augmentation, animation deformity in patients undergoing breast reconstruction is certainly more prevalent and likely more severe. Spear et al reported 15% of breast augmentation patients presenting with moderate to severe deformity while studies in reconstructive patients have reported up to 80% with moderate to severe deformity (2,14). In our own series of breast reconstruction patients, we have found an average nipple displacement of 2.12 cm (8).…”
Section: What Is Animation Deformity?mentioning
confidence: 50%
See 1 more Smart Citation
“…Although initially described in patients undergoing breast augmentation, animation deformity in patients undergoing breast reconstruction is certainly more prevalent and likely more severe. Spear et al reported 15% of breast augmentation patients presenting with moderate to severe deformity while studies in reconstructive patients have reported up to 80% with moderate to severe deformity (2,14). In our own series of breast reconstruction patients, we have found an average nipple displacement of 2.12 cm (8).…”
Section: What Is Animation Deformity?mentioning
confidence: 50%
“…Animation deformity is a common and distressing sequelae of breast reconstruction, estimated to occur in anywhere from 75-100% of sub-pectoral breast reconstructions (1,2). Animation deformity is caused by contraction of the pectoralis muscle against the breast implant, causing it and the overlying breast shape to unnaturally shift with muscle contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Without the breast parenchyma to separate the mastectomy skin from the pectoralis muscle, the skin becomes tethered to the underlying muscle. Any activation of the pectoralis can cause significant deformity of a patients' chest, with lateral breast displacement (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…While many patients achieve a satisfactory aesthetic result, an overwhelming proportion have been reported to develop some degree of animation deformity (Figure 1). Animation deformity refers to the tethering of the patient's mastectomy flap skin to the underlying pectoralis major muscle, resulting in both visible contraction and lateral displacement of the entire breast mound with any activation of the pectoralis muscle (1,2). This can be painful for many patients and extremely visibly displeasing.…”
Section: Introductionmentioning
confidence: 99%
“…While two-stage sub-pectoral implant reconstruction gave reasonable results, it was apparent on critical appraisal, that patients experience significant physical limitations secondary to sub-pectoral implant placement. Most patients exhibit some degree of animation deformity during activity, particularly during adduction of the humerus (12,(25)(26)(27). Sub-pectoral implant placement may also have more serious morbidity.…”
Section: Introductionmentioning
confidence: 99%